Diagnostic testing for Legionnaires' disease - David M. Pierre; Julianne Baron; Victor L. Yu; Janet E. Stout (BMC, 2017)
Abstract Legionnaires' disease is commonly diagnosed clinically using a urinary antigen test. The urinary antigen test is highly accurate for L. pneumophila serogroup 1, however other diagnostic tests should also be utilized in conjunction with the urinary antigen as many other Legionella species and serogroups are pathogenic. Culturing of patient specimens remains the gold standard for diagnosis of Legionnaires' disease. Selective media, BYCE with the addition of antibiotics, allows for a high sensitivity and specificity. Culturing can identify all species and serogroups of Legionella. A major benefit of culturing is that it provides the recovery of a patient isolate, which can be used to find an environmental match. Other diagnostic tests, including DFA and molecular tests such as PCR and LAMP, are useful tests to supplement culturing. Molecular tests provide much more rapid results in comparison to culture, however these tests should not be a primary diagnostic tool given their lower sensitivity and specificity in comparison to culturing. It is recommended that all laboratories develop the ability to culture patient specimens in-house with the selective media.